National and cultural symbolism of zoo-anthropomorphic creatures in Ukrainian myphological picture of the world - Kryzhko, Olena (Res LOGOS, 2019)
The article analyses the myphopoetic origins of the Ukrainian national and cultural symbolism of zoo-anthropomorphic creatures. It examines how animal names create ethnic symbols, i.e. the peculiar fragments of the Ukrainian mythological picture of the world. The national concepts of zoonyms and their implementation are described in the Ukrainian mythological system. The attention is given to zoo-anthropomorphic creatures: their etiologic function and having their own national and cultural symbolism, an axiological identification of good / evil in the explanation of the universe, the manner they are semanticised by the symbolism and value categories of the Ukrainian myphopoetic consciousness in the plot lines of Ukrainian myths and legends.
Keywords: Ukrainian national and cultural symbolics; zoo-anthropomorphic creatures; ethnic symbols; Ukrainian mythological picture of the world; national concept; zoonyms